2020
DOI: 10.3390/ma13071587
|View full text |Cite
|
Sign up to set email alerts
|

Application of Life-Dependent Material Parameters to Fatigue Life Prediction under Multiaxial and Non-Zero Mean Loading

Abstract: This study presents the life-dependent material parameters concept as applied to several well-known fatigue models for the purpose of life prediction under multiaxial and non-zero mean loading. The necessity of replacing the fixed material parameters with life-dependent parameters is demonstrated. The aim of the research here is verification of the life-dependent material parameters concept when applied to multiaxial fatigue loading with non-zero mean stress. The verification is performed with new experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The previously presented calculation models contain material properties that are constant values. Meanwhile, some research results indicate that the fatigue properties of the material may change with the number of cycles, and it is postulated that this effect should be taken into account in calculation algorithms [14,16,23,24]. Some proposals extend the applicability of the Goodman, Gerber, and other mentioned models in the range of lowcycle fatigue by taking into account the current number of failure cycles in transformation models [25,26].…”
Section: Transformation Model For the Mean Load Value In Relation To ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The previously presented calculation models contain material properties that are constant values. Meanwhile, some research results indicate that the fatigue properties of the material may change with the number of cycles, and it is postulated that this effect should be taken into account in calculation algorithms [14,16,23,24]. Some proposals extend the applicability of the Goodman, Gerber, and other mentioned models in the range of lowcycle fatigue by taking into account the current number of failure cycles in transformation models [25,26].…”
Section: Transformation Model For the Mean Load Value In Relation To ...mentioning
confidence: 99%
“…It is also pointed out in the literature that the limitation of the dependence of the Goodman and Gerber model is significant at the fatigue limit level. Gasiak and Pawliczek [13] and Kluger et al [14] showed that the parameters of computational models considering the mean value change with the number of cycles. Verification of the computational models for so-called life-dependent material parameters was performed for specimens made of S355 alloy steel [13,14] and 7075-T651 aluminum alloy [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case as well, the fatigue strength is estimated [ 20 , 21 ] and crack propagation is observed [ 22 ]. A new proposition for estimating the fatigue strength, based on factoring in the variability in material parameters, was presented in [ 10 , 23 ]. In these works, the models were verified based on the findings from studies on fatigue in aluminium alloys.…”
Section: Introductionmentioning
confidence: 99%